Left-right asymmetry and minimal coupling - Marques, G. C.; Spehler, D. (American Institute of Physics (AIP), 1996)
In this paper we deal with an alternative approach to the description of massless particles of arbitrary spin. Within this scheme chiral components of a spinor field are regarded as fundamental quantities and treated as independent field variables. The free field Lagrangian is built up from the requirement of chiral invariance; This formulation is parallel to the neutrino theory and allows for a formulation that generalizes, to particles of arbitrary spin, the two-component neutrino theory. We achieve a spinor formulation of electrodynamics. In the case of the photon, the nonzero helicity components satisfy Weyl's equations and are associated to observables (electromagnetic fields) whereas the zero helicity components are related to nonobservables (electromagnetic potentials). Within the spinor formulation of electrodynamics the minimal coupling substitution follows as a consequence of the linearity of the interaction and the preference of nature for chiral components, that is, of the left-right asymmetry of nature. (C) 1996 American Institute of Physics.